2021
DOI: 10.3390/antiox10111753
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics to Diagnose Oxidative Stress in Perinatal Asphyxia: Towards a Non-Invasive Approach

Abstract: There is a need for feasible and non-invasive diagnostics in perinatal asphyxia. Metabolomics is the study of small molecular weight products of cellular metabolism that may, directly and indirectly, reflect the level of oxidative stress. Saliva analysis is a novel approach that has a yet unexplored potential in metabolomics in perinatal asphyxia. The aim of this review was to give an overview of metabolomics studies of oxidative stress in perinatal asphyxia, particularly searching for studies analyzing non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…It also increases the generation of sarcosine and glycine in several organisms [68] . The activation and enhancement of the urea cycle, alanine, and valine in this study were reportedly found to be related to increased oxidative stress in perinatal asphyxia [56] .…”
Section: Discussionsupporting
confidence: 58%
“…It also increases the generation of sarcosine and glycine in several organisms [68] . The activation and enhancement of the urea cycle, alanine, and valine in this study were reportedly found to be related to increased oxidative stress in perinatal asphyxia [56] .…”
Section: Discussionsupporting
confidence: 58%
“…It is important to design non-invasive tools tailored to the characteristics of newborns, and saliva analysis has unexplored potential. This Special Issue includes a literature review providing an overview of metabolomics studies of oxidative stress in perinatal asphyxia, particularly seeking studies analyzing non-invasively collected biofluids such as saliva [ 5 ]. While changes in oxidative stress-related salivary metabolites have been reported in adults, the utility of this approach in perinatal asphyxia has yet to be explored.…”
mentioning
confidence: 99%